Improving the Physical Basis for Updraft Dynamics in Deep Convection Parameterizations. (22nd February 2021) - Peters, J. M.; Morrison, H.; Zhang, G. J.; Powell, S. W.
Abstract: This article presents a new deep convective parameterization that determines cloud characteristics based on a specified cloud size distribution. The vertical profiles of cloud properties are determined by analytic equations, which formulate entrainment with an inverse relationship to cloud width. In line with recent studies of large eddy simulations (LES), cloud widths are assumed to be constant with height and vertical mass flux ( M ) characteristics of the clouds are therefore regulated by the vertical velocity profile. The parameterization is configured to work with existing cloud base M closure formulations, with the closure predicting the total cloud area rather than the cloud base M directly. Analytic formula are also used to connect the vertical wind shear magnitude to the cloud size distribution, wherein larger shear magnitudes result in more numerous large updrafts than weaker shear magnitudes, which is in line with recent research results. The parameterization is compared against 10 deep convective LES with varying thermodynamic and vertical wind shear profiles. Results show dramatic improvements in the prediction of normalized M, detrainment, and the properties of detrained air over the existing Zhang and McFarlane (1995) scheme. In particular, the new model is able to correctly portray the transition from a bottom‐heavy M profile in weakly sheared environments, to a top‐heavy M profile in strongly sheared environments. Plain Language Summary: This study presents a new avenue for representing thunderstorms in climate and global forecast models. The model assumes that cloud widths follow an exponential distribution, with many narrow clouds and few wide clouds. The properties of cloud cores are represented by analytic equations, which saves computational expense. Entrainment is assumed to be inversely proportional to clouds' widths, which is consistent with known cloud behavior. The effects of vertical wind shear on the cloud size distribution are included. Cloud properties and behavior in the new parameterization agree well with high resolution simulations of deep convection. Key Points: Improved dynamical assumptions in cumulus parameterization Incorporating vertical wind shear into cumulus parameterization Analytic equations for vertical mass flux and vertical velocity